2022
DOI: 10.3390/antibiotics11060746
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Antibiotic Consumption Coincided with Reduction in Bacteremia Caused by Bacterial Species with Respiratory Transmission Potential during the COVID-19 Pandemic

Abstract: Nonpharmaceutical interventions implemented during the COVID-19 pandemic (2020–2021) have provided a unique opportunity to understand their impact on the wholesale supply of antibiotics and incidences of infections represented by bacteremia due to common bacterial species in Hong Kong. The wholesale antibiotic supply data (surrogate indicator of antibiotic consumption) and notifications of scarlet fever, chickenpox, and tuberculosis collected by the Centre for Health Protection, and the data of blood cultures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 67 publications
(89 reference statements)
1
13
0
1
Order By: Relevance
“…The episode-based records of our patients were retrieved from the Clinical Data Analysis and Reporting System (CDARS), an electronic database of health records under the governance of the Hospital Authority, as previously described [ 22 , 23 ]. The quarterly number of patient days in our hospitals was also retrieved from CDARS.…”
Section: Methodsmentioning
confidence: 99%
“…The episode-based records of our patients were retrieved from the Clinical Data Analysis and Reporting System (CDARS), an electronic database of health records under the governance of the Hospital Authority, as previously described [ 22 , 23 ]. The quarterly number of patient days in our hospitals was also retrieved from CDARS.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 22 studies, 11 studies described the changes in the prevalence of MRSA infections [20] , [25] , [26] , [27] , [32] , [36] , [37] , [41] , [44] , [45] , [47] with eight of them reporting increase in the prevalence of MRSA infections [25] , [26] , [27] , [37] , [41] , [44] , [45] , [47] . Eight studies showed the changes in MRSA infections during COVID-19 pandemic using incidence density per 1,000 or 10,000 patient-days [21] , [23] , [29] , [31] , [35] , [38] , [46] , [48] , and four of them demonstrated increase in the incidence density of MRSA infections during the pandemic [21] , [23] , [46] , [48] . Overall, most of the studies (54.5%) reported increase in the prevalence/incidence of MRSA infections/colonization during the COVID-19 pandemic and the increase ranged from 4.6% to 200.0%.…”
Section: Resultsmentioning
confidence: 99%
“…The episode-based records of all inpatients were retrieved from the Clinical Data Analysis and Reporting System (CDARS), an electronic database of health records under the governance of the Hospital Authority, as previously described [ 39 ]. Briefly, a unique hospital number was assigned to each hospital admission.…”
Section: Methodsmentioning
confidence: 99%